2008
DOI: 10.1152/ajpheart.00541.2008
|View full text |Cite
|
Sign up to set email alerts
|

Age impairs Flk-1 signaling and NO-mediated vasodilation in coronary arterioles

Abstract: Impairment of flow-induced vasodilation in coronary resistance arterioles may contribute to the decline in coronary vasodilatory reserve that occurs with advancing age. This study investigated the effects of age on flow-induced signaling and activation of nitric oxide (NO)-mediated vasodilation in coronary resistance arterioles. Coronary arterioles were isolated from young (approximately 6 mo) and old (approximately 24 mo) male Fischer-344 rats to assess vasodilation to flow, vascular endothelial growth factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
40
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 45 publications
8
40
1
Order By: Relevance
“…1). These data confirm previous results from our laboratory demonstrating an age-related reduction in NO-mediated endotheliumdependent dilation (21).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…1). These data confirm previous results from our laboratory demonstrating an age-related reduction in NO-mediated endotheliumdependent dilation (21).…”
Section: Resultssupporting
confidence: 93%
“…Previous studies have indicated that NO-mediated endothelial function declines with advancing age (26,43,49), and recent reports have shown a similar impairment in endothelium-mediated vasodilation in the coronary microvasculature (7,21). In the present study, we have demonstrated for the first time an age-induced decline in flow-induced NO production, as evidenced by diminished DAF fluorescence in isolated coronary arterioles of aged rats (Fig.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Although total eNOS was not affected by estrogen status, phosphorylation of eNOS protein (serine 1177) was increased in arterioles from middle-aged and old females after estrogen replacement. In coronary arterioles from male rats, we have previously reported that advancing age impairs flowinduced vasodilation through reductions in Flk-1 activation and PI3-kinase/Akt signaling (23). Similar to our findings in coronary arterioles from old male rats, our current results indicate that basal NO remained constant (Table 2) despite changes in NO-mediated dilation that occurred with advancing age and manipulation of circulating estrogen.…”
Section: Discussionsupporting
confidence: 90%